CLUSTERING DISTRICT/CITY IN WEST KALIMANTAN BASED ON FACTORS CAUSING STUNTING USING K-HARMONIC MEANS METHOD - Imanni, Rahmania Andarini Hatti; Sulistianingsih, Evy; Perdana, Hendra (Jurnal Statistika Universitas Muhammadiyah Semarang, 2024)
Stunting is a chronic nutritional problem caused by inadequate dietary intake over time. The results of the Indonesian Nutrition Status Survey (SSGI) 2021 show that the percentage of stunting in West Kalimantan is 29.8%, higher than the national average. Based on the high number of stunting cases in West Kalimantan, it is necessary to group districts/cities in West Kalimantan based on the factors that cause stunting. This study aims to analyze the clustering of districts/cities in West Kalimantan based on the factors that cause stunting using the K-Harmonic Means method and analyze the number of optimal clusters using the silhouette coefficient. The percentage of households without access to clean drinking water , the rate of exclusive breastfeeding , the percentage of low birth weight babies born safely , the percentage of households without proper sanitation facilities  in 2021 are the variables analyzed in this study. The analysis results show that the optimal number of clusters is 4 with a silhouette coefficient value of 0.744, indicating a solid structure in the grouping. Cluster 1 is a cluster with a very high causal factor for stunting. The most influential factors in cluster 1 are households without access to clean drinking water, lack of exclusive breastfeeding, and low birth babies born safely.